PENGARUH PROMOSI TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA DINAS PENDIDIKAN KABUPATEN KUTAI KARTANEGARA - Muhammad Fahrizal (Jurnal Paradigma (JP), 2017)
To enhance employee productivity in Education Department of Kutai Kartanegara, the office leader need to deliver attention to whom has the best track record. Rewarding is a way to endorse the employee to pursue their future goals. This article is intended to explain the influence of promotion to the employee productivity.